2022
DOI: 10.1128/spectrum.02207-21
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater-Based SARS-CoV-2 Surveillance in Northern New England

Abstract: Despite vaccination efforts, the delta and omicron variants of SARS-CoV-2 have caused global surges of COVID-19. As the COVID-19 pandemic continues, it is important to find new ways of tracking early signs of SARS-CoV-2 outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…The procedures used for viral detection have been less studied and standardization is still needed. This work highlighted the detection of SARS-CoV-2 in 11 positive samples (58%) and a higher rate of positivity was detected at 47% for the N gene (9/19) among 19 wastewater samples collected from the WWTP 1 plant and other treatment plants such as the WWTP 3 plant in central Tunis area and the WWTP 4 and WWTP 5 treatment plants in the Sahel area by multiplex real-time RT-PCR for four SARS-CoV-2 specific genes namely E, RdRp, S and N. Our results are concordant with those recorded by the first study on the prevalence of SARS-CoV-2 in wastewater that appeared on 30 March 2020 in the Netherlands (58%) (Medema et al, 2020 ), and close to those detected in Brazil (43.63%) (de Sousa et al, 2022 ) and in Northern New England (61.8% samples using RT-qPCR and 68.9% samples using RT-ddPCR) (Toledo et al, 2022 ). However, our results contradict those recorded in Tehran, which revealed that SARS-CoV-2 RNA was detectable in 100% (N test) and 81% (ORF1ab test) of 91 wastewater samples (Amereh et al, 2022 ).…”
Section: Discussionsupporting
confidence: 88%
“…The procedures used for viral detection have been less studied and standardization is still needed. This work highlighted the detection of SARS-CoV-2 in 11 positive samples (58%) and a higher rate of positivity was detected at 47% for the N gene (9/19) among 19 wastewater samples collected from the WWTP 1 plant and other treatment plants such as the WWTP 3 plant in central Tunis area and the WWTP 4 and WWTP 5 treatment plants in the Sahel area by multiplex real-time RT-PCR for four SARS-CoV-2 specific genes namely E, RdRp, S and N. Our results are concordant with those recorded by the first study on the prevalence of SARS-CoV-2 in wastewater that appeared on 30 March 2020 in the Netherlands (58%) (Medema et al, 2020 ), and close to those detected in Brazil (43.63%) (de Sousa et al, 2022 ) and in Northern New England (61.8% samples using RT-qPCR and 68.9% samples using RT-ddPCR) (Toledo et al, 2022 ). However, our results contradict those recorded in Tehran, which revealed that SARS-CoV-2 RNA was detectable in 100% (N test) and 81% (ORF1ab test) of 91 wastewater samples (Amereh et al, 2022 ).…”
Section: Discussionsupporting
confidence: 88%
“…Our data are corroborated by Vogels et al who found similar results from an analysis of 172 nasopharyngeal samples [20]. This slight difference between N1 and N2 primer sets has been corroborated in other studies [21]. Together, the consistently higher sensitivity of filters vs direct extracts combined with the efficiency of filtration make a strong case that filtration is a better method for the detection of SARS CoV-2 in wastewater.…”
Section: Plos Onesupporting
confidence: 91%
“…Moreover, as rural communities often lack the resources for broader-scale clinical testing, WBE can help sustain rural community health. Unfortunately, WBE has mainly focused on urban areas and larger cities, leaving rural communities with reduced access to this critical data (11,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%